Implementation of Digital Game-Based Learning Approach in CTU281 subject: the impact on self-motivation among graphic students in UiTM Melaka / Ilinadia Jamil - Jamil, Ilinadia (Faculty of Art and Design, 2020)
Interactive multimedia technology and digital game approach in learning environment can foster a more effective and interesting learning process, especially among university students. This study was made with the implementation of digital game-based learning approach for the final project of Diploma in Graphic and Digital Media (AD111) students from UiTM Alor Gajah, Melaka who took the Islamic Beauty and Creativity subject (CTU281) to see the impact and effectiveness of digital game-based learning on students' academic performance and self-motivation. The study sample was taken starting from the process of students completing their final project until the Islamic Art and Communication Festival (ISAC 2016) program takes place.The ISAC 2016 program is a platform organized by the Academy of Contemporary Islamic Studies (ACIS) in collaboration with the Faculty of Communication and Media Studies (FKPM) and the Faculty of Art and Design (FSSR) which aims to reduce students' failure statistics in CTU course code as well as helping students to pass in this compulsory subject. This program involves all Semester 3 students of Faculty of Art and Design, UiTM Cawangan Melaka who took the CTU281 subject and also the students from Faculty of Communication and Media Studies who took the CTU271 subject. However, this study only involved 14 groups of Diploma in Graphic and Digital Media (AD111) students, UiTM Cawangan Melaka who took the CTU281 subject. The results of the study found that the students were very motivated with the results of their projects whereby two projects from the AD111 group were named as the Best Projects. In conclusion, the failure statistics for CTU281 subject code among graphics students last semester can realistically be reduced with the implementation of digital game-based learning approach as this approach helped students pass in this subject as well as increase the students' potential to be more positive and upgrading their self-motivation.